2011
DOI: 10.1136/gut.2011.239301.471
|View full text |Cite
|
Sign up to set email alerts
|

In the treatment of flares of inflammatory bowel disease, intravenous hydrocortisone causes greater falls in blood potassium and more severe episodes of hypokalaemia than methylprednisolone

Abstract: Introduction Corticosteroids are important treatments for acute exacerbations of infl ammatory bowel disease (IBD). In severe fl ares, or when oral steroid has proven unsuccessful, high dose intravenous steroid can be given in a hospital setting. Two intravenous corticosteroids are in common usage: hydrocortisone (HC) and methylprednisolone (MP). As well as the therapeutic glucocorticoid effect, both agents have mineralocorticoid effect. The mineralocorticoid effect of HC is greater than MP at the doses common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Intravenous corticosteroids such as hydrocortisone 100 mg four times daily or methylprednisolone 60 mg every 24 hours are the cornerstone of treatment of ASUC 106 203–205. Methylprednisolone has less mineralocorticoid effect than hydrocortisone at these doses and so causes significantly less hypokalaemia 206. There is no real advantage from giving higher doses and a bolus injection is as effective as a continuous infusion 207.…”
Section: Ulcerative Colitismentioning
confidence: 99%
“…Intravenous corticosteroids such as hydrocortisone 100 mg four times daily or methylprednisolone 60 mg every 24 hours are the cornerstone of treatment of ASUC 106 203–205. Methylprednisolone has less mineralocorticoid effect than hydrocortisone at these doses and so causes significantly less hypokalaemia 206. There is no real advantage from giving higher doses and a bolus injection is as effective as a continuous infusion 207.…”
Section: Ulcerative Colitismentioning
confidence: 99%
“…This is slightly higher than Wiles et al, who reported a rate of 45% (76/170 patients). 14 Of note, they described marked differences in incidence of patients treated with IVHC vs IVMP (69% vs 11%, P < 0.0001), with similar rates of requirement for potassium supplementation. Our data also demonstrated this (67% vs 56%, P = 0.04, respectively) and IVMP was shown to be an independent predictor of reduced hypokalemia OR = 0.49, P = 0.005.…”
Section: Discussionmentioning
confidence: 94%
“…13 IVHC use in acute severe colitis has been shown to have an increased incidence of hypokalemia compared with IVMP. 14 Hypokalemia is known to predispose to colonic dilatation. 15 Additionally, it has the practical benefit of a once daily dosing regimen, which has been shown to be no different than continuous infusions in terms of efficacy and safety in acute severe UC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no additional benefit for higher doses than methylprednisolone 60 mg/day beyond 7-10 days of therapy as it may actually increase complications risk. Hydrocortisone (100 mg every 6 h) has been associated with higher rates of hypokalaemia [36].…”
Section: First Line Medical Therapy: Intravenous Corticosteroidsmentioning
confidence: 99%